Increasing Academic Performance by Handling Procrastination among Students through Cognitive Behavioral Therapy - Rehana Aslam; Sarwat Sultan; Mishal Zahra (Journal of Management Practices, Humanities and Social Sciences, 2024)
The study provides insights into a valuable dynamic of the role of transformational leadership on employees' innovative performance in colleges in Punjab, Pakistan. By applying quantitative data, the study emphasizes how transformational leadership influences innovative performance in educational settings. By applying the qualitative method, the study fills the critical gap in understanding how leadership and employee performance are connected. Using the hierarchical regression technique, the paper examines the role of transformational leadership in employees' innovative performance at the college level in Punjab, Pakistan. Data was gathered through a standard questionnaire from the faculty and administrative staff of public (N = 93) and private colleges (N = 107), and the data was analyzed using a quantitative approach. The survey items comprised in the survey were associated with transformational leadership, innovative performance, organizational support for innovation, job satisfaction and work environment. Results are based on self-administered questionnaires and were analyzed by correlation and regression methods, which reveals a significant positive relationship between transformational leadership and employees' innovative performance. The outcomes highlight the significance of visionary leadership in promoting a creative and innovative setting at educational institutes. The findings are further discussed in the context of theory and practice, which have implications for leadership development programs within higher education. Academic performance is crucial as it not only reflects a student's understanding and mastery of the material but also influences future educational and career opportunities. This quasi-experimental study aimed to increase the academic performance of college students by handling their procrastination through cognitive behaviour therapy (CBT). A sample of 40 female college students aged 18-25 years who scored high on the procrastination scale was recruited. Randomly categorized experimental and control groups with 20 participants in each provided data on procrastination and academic performance scales at three times; baseline (T1), after treatment (T2), and follow-up (T3). CBT was administered to the participants in eight sessions, one session weekly. The findings showed a significant difference in the levels of procrastination and academic performance of students between the scores of pre-, post, and follow-up testing of CBT. Findings revealed asignificant decrease in procrastinated behaviour from T1 to T3 and an increase in the academic performance of students after intervention from T1 to T3. The findings have implications for teachers and psychologists in handling the problem of procrastination in terms of the academic performance of students. Psychologists and counsellors should offer workshops on procrastination strategies, emphasizing the importance of early intervention to enhance academic outcomes.